Marginality Associated with Interorganizational Linking Process, Productivity, and Satisfaction - Pruden, Henry O.; Stark, B. J. (Academy of Management Journal, 1971)
The article reports on the concept of marginality as it applies to industrial organization and industrial management. The author focuses on ways in which marginality affects job satisfaction and industrial productivity. A study investigating how marginality impacts the interorganizational linking process is analysed. The internorganizational linking processes has to do with the decision making and communicative behaviors of salespersons. The study results indicate that there is a correlation between labor productivity and marginality. The affect of marginality on performance standards is also discussed.